PRAKTIK NIKAH SIRI ONLINE DITINJAU DARI HUKUM POSITIF YANG BERLAKU DI INDONESIA - Tsanya Nofrianti Sukardi (2023)
This study aims to analyze the practice of online siri marriage in terms of Islamic Law and Legislation. This research is empirical normative research with the problem approach method used is the statute approach, case approach, and conceptual approach. This research shows that online siri marriage sites have deviated and are not in accordance with Islamic Law and Positive Law. So that the legality of online siri marriage sites has violated religious and state laws, so their existence is not allowed. Then the juridical consequences that will be caused by online siri marriage service providers, namely the siri marriage site will be blocked according to the Minister of Communication and Informatics Law No. 19 of 2004. As for parties who carry out unregistered marriages online, they do not get legal protection because the marriage is considered to have never happened in the eyes of the law. This research suggests the need for firmness regarding the regulation of unregistered marriages and online unregistered marriages and strict sanctions against perpetrators of online unregistered marriage services.